Profil Gaya Berpikir Peserta Didik dalam Menyelesaikan Soal Matematika pada Materi Trigonometri - Intan Larasati; Kiki Nia Sania Effendi (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
The purpose of this research was to describe the mind style of students in solving mathematics problem at trigonometry material. The research was conducted in one of high school in Karawang district for 33 students in class XI IPA 1. Data’s collection of this research was obtained by giving mind style’s delineator, mathematics problem’s test, and interview. The subjects of this research were 4 students whom selected by using purposive sampling technique as the representation of each type of mind style. The data analysis of this research was using Miles and Huberman’s interactive model through the stages of data’s reduction, data’s display, and verification. The results of this research showed that there were 7 students had Concrete Sequential’s mind style, 6 students had Abstract Sequential’s mind style, 14 students had Concrete Random’s mind style, and 6 other students had Abstract Random’s mind style. Therefore, it can be concluded that the dominant’s mind style of students in XI IPA 1 was Abstract Random’s mind style.